2016
DOI: 10.1038/icb.2016.16
|View full text |Cite
|
Sign up to set email alerts
|

Linking the T cell receptor to the single cell transcriptome in antigen‐specific human T cells

Abstract: Heterogeneity of T cells is a hallmark of a successful adaptive immune response, harnessing the vast diversity of antigen-specific T cells into a coordinated evolution of effector and memory outcomes. The T cell receptor (TCR) repertoire is highly diverse to account for the highly heterogeneous antigenic world. During the response to a virus multiple individual clones of antigen specific CD8+ (Ag-specific) T cells can be identified against a single epitope and multiple epitopes are recognised. Advances in sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
97
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 120 publications
(99 citation statements)
references
References 33 publications
2
97
0
Order By: Relevance
“…We tested this hypothesis by comparing individual cell and bulk profiles from BRI-4.13 (19), an islet antigen-reactive CD4+ T cell clone from an individual with T1D (Materials and Methods). Although single cell transcript profiling has been successfully used with several cell types (36), less is known (37) about the performance of single cell techniques with antigen-specific T cells, which contain very limited amounts of RNA. In our experiments, we detected non-linearity between individual cell and bulk profiles in expression of low abundance genes, indicating that genes expressed at low levels are less likely to be detected at the single cell level than in a bulk measurement (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…We tested this hypothesis by comparing individual cell and bulk profiles from BRI-4.13 (19), an islet antigen-reactive CD4+ T cell clone from an individual with T1D (Materials and Methods). Although single cell transcript profiling has been successfully used with several cell types (36), less is known (37) about the performance of single cell techniques with antigen-specific T cells, which contain very limited amounts of RNA. In our experiments, we detected non-linearity between individual cell and bulk profiles in expression of low abundance genes, indicating that genes expressed at low levels are less likely to be detected at the single cell level than in a bulk measurement (Figure 1A).…”
Section: Resultsmentioning
confidence: 99%
“…1A), which is generated through a series of somatic rearrangements and mutations that allow for more than 10 18 possible sequences (Davies et al , 1975; Edelman, 1959; Elhanati et al , 2015). Single-cell RNA-sequencing (scRNA-seq) offers a particularly powerful way to study adaptive immune cells, simultaneously allowing both for capture of quantitative gene expression as well as repertoire sequence information (Eltahla et al , 2016; Stubbington et al , 2016). By coupling gene expression with specific BCRs, exciting opportunities emerge in studying B-cell biology that are not approachable with bulk RNA-seq and repertoire studies, such as characterizing at single-cell resolution the transcriptional heterogeneity underlying BCR affinity maturation and receptor specificity.…”
Section: Introductionmentioning
confidence: 99%
“…TraCeR [62] was the first tool for T cell receptor (TCR) reconstruction from scRNA-seq, followed quickly by VDJPuzzle [63]. Whereas, BASIC is currently the only algorithm designed specifically for B cells and the only approach that performs its own assembly of the V(D)J receptor sequence [64].…”
Section: Immune Repertoirementioning
confidence: 99%
“…Already, this innovative combination showed that the T cell clonotypes responding to a murine Salmonella infection come from diverse T cell compartments and it identified a previously unappreciated repertoire diversity within HCV specific T cells before and after ex vivo cell culture [62,63]. Prior interrogation of both questions was impossible, and it will be very exciting to see what else this powerful new combination brings in the future.…”
Section: Immune Repertoirementioning
confidence: 99%